A Dance Work Representing Ida Bagus Blangsinga’s Life Journey (The Maestro of Kebyar Duduk Dance in Blangsinga Style) - Ida Ayu Triana Titania Manuaba; I Wayan Dibia; I Ketut Sariada (Institut Seni Indonesia Denpasar, 2022)
This work aims to represent the figure of Ida Bagus Blangsinga, a master of the Kebyar Duduk dance in Blangsinga style. The method of creation used in this work uses the creation method which includes assessment, experimentation, and formation. This method is easily understood by the stylist to express and visualize several scenes in the work. The form of the chosen work is a new creation dance, because it provides space for development according to the wishes of the stylist. This work is danced by six female dancers and one male dancer using soft make-up and fashion that supports each part of the work. This work uses the fan and reverberation properties. This dance is made as a contribution to the development of Balinese dance especially to the new generation.